The role of organizational fairness and motivation in the relationship between budget participation and managerial performance: A conceptual paper - Zainuddin, Suria; Isa, Che Ruhana (American-Eurasian Network for Scientific Information, Jordan, 2011)
The debates related to the role of budget participation in organizations have attracted the attention of management accounting researchers for decades. However studies examining the relationship between budget participation and performance have found inconsistent results ranging from positive relationship to negative relationship. The inconsistent findings have encouraged researchers to further investigate for the existence of mediating variables in the relationship between budget participation and managerial performance. In this study, a more comprehensive model of participative budgeting that incorporates the element of fairness and motivation is proposed. Participation is modeled to have an indirect effect on performance through two intervening variables of organizational fairness and motivation. In particular, the objective of this study is to examine the relationship between budget participation and managerial performance. This study also aims to examine the mediating role of organizational fairness and motivation in the relationship between budget participation and managerial performance.